2005
DOI: 10.1074/jbc.m506771200
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of Tumor Necrosis Factor Receptor-associated Factor Family Proteins to Apoptosis Signal-regulating Kinase 1 Signalosome Is Essential for Oxidative Stress-induced Cell Death

Abstract: Apoptosis signal-regulating kinase 1 (ASK1) plays a pivotal role in oxidative stress-induced cell death. Reactive oxygen species disrupt the interaction of ASK1 with its cellular inhibitor thioredoxin and thereby activates ASK1. However, the precise mechanism by which ASK1 freed from thioredoxin undergoes oligomerization-dependent activation has not been fully elucidated. Here we show that endogenous ASK1 constitutively forms a high molecular mass complex including Trx (ϳ1,500 -2,000 kDa), which we designate A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
205
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(224 citation statements)
references
References 58 publications
16
205
1
2
Order By: Relevance
“…It has been well documented that TNF-a-induced TRAF2-ASK1 complex is required for ASK1 activation Liu et al, 2000;Noguchi et al, 2005). We and another group also found that GSTP1-1 inhibited the enzymatic activity of ASK1 in vivo (Yin et al, 2001) but not in vitro (Cho et al, 2001).…”
Section: Gstp1-1 Regulates Traf2-induced Ask1 Activationmentioning
confidence: 55%
See 3 more Smart Citations
“…It has been well documented that TNF-a-induced TRAF2-ASK1 complex is required for ASK1 activation Liu et al, 2000;Noguchi et al, 2005). We and another group also found that GSTP1-1 inhibited the enzymatic activity of ASK1 in vivo (Yin et al, 2001) but not in vitro (Cho et al, 2001).…”
Section: Gstp1-1 Regulates Traf2-induced Ask1 Activationmentioning
confidence: 55%
“…Previous studies suggested that TNF-atriggered TRAF2-ASK1 interaction was dependent on ROS. Some ROS scavengers, such as NAC, inhibited the disassociation of ASK1-Trx and thus suppressed TNF-a-elicited cell apoptosis Liu et al, 2000;Noguchi et al, 2005). However, our study demonstrated that the interaction of GSTP1-1 and TRAF2 was not influenced by NAC or BSO in resting or TNF-a-treated HeLa cells, and suggested that the mechanism of TNF-a-induced disassociation of TRAF2-GSTP1-1 and ASK1-Trx may be different.…”
Section: Gstp1-1 Modulates Tnf-a Signalingmentioning
confidence: 56%
See 2 more Smart Citations
“…13 Role of ASK1 has also been well established for oxidative stressinduced JNK activation. 14 On the other hand, there are conflicting reports on whether RNS activate or inhibit ASK1. 7,15 Here we explored the involvement of ASK1 in RNS-induced JNK activation and cell death.…”
Section: Resultsmentioning
confidence: 99%